Some properties of light weight concrete containing carbon fiber (Iraqi Journal of Civil Engineering, 2009)
Abstract:-This investigation studies the mechanical characteristics of carbon fiber reinforcedlight weight aggregate concrete, containing different percentages of fiber. The effect ofusing high range water reducing agent (SP) with 8% silica fume (SF) and 8% highreactivity Metakaolin (HRM), as a partial replacement by weight of cement, on thebehavior of (LWA) concrete is also studied.This investigation was carried out using several tests. These tests were workability freshand hardened density, compressive strength, splitting tensile strength and modulus ofrupture. Tests were performed for specimens at ages of (7,28,60,90 and 180) days . Thetest results indicated that the inclusion of carbon fiber to the light weight concrete mix didnot affect the compressive strength significantly, while the splitting tensile strength andthe modulus of rupture were improved significantly. The addition of silica fume andmetakaolin improves the compressive, splitting tensile , and modulus of rupture strengthsof carbon fiber light weight concrete. The average improvement was about (26.5%, 71%and 73 %) respectively for carbon fiber LWA concrete containing silica fume and (28%,72% and 75%) respectively for carbon fiber LWA concrete containing high reactivitymetakaolin.